2021
DOI: 10.1021/acsptsci.1c00094
|View full text |Cite
|
Sign up to set email alerts
|

Selective Integrin Ligands Promote Cell Internalization of the Antineoplastic Agent Fluorouracil

Abstract: Drug conjugates consisting of an antineoplastic drug and a targeting receptor ligand could be effective to overcome the heavy side effects of unselective anticancer agents. To address this need, we report here the results of a project aimed to study agonist and antagonist integrin ligands as targeting head of molecular cargoes for the selective delivery of 5-fluorouracil (5-FU) to cancer or noncancer cells. Initially, two fluorescent β-lactam-based integrin ligands were synthesized and tested for an effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Among the previously described small-molecule drug conjugates (SMDC) based on or inspired by peptides, there are only a few conjugates known for targeting the integrins ( Dal Corso et al, 2016 ; Baiula et al, 2021 ; Lerchen et al, 2022 ; Slack et al, 2022 ), particularly α V β 3, with non-peptide homing devices. Such RGD mimetics provide additional possibilities of introducing structural elements and are metabolically more stable than peptides.…”
Section: Resultsmentioning
confidence: 99%
“…Among the previously described small-molecule drug conjugates (SMDC) based on or inspired by peptides, there are only a few conjugates known for targeting the integrins ( Dal Corso et al, 2016 ; Baiula et al, 2021 ; Lerchen et al, 2022 ; Slack et al, 2022 ), particularly α V β 3, with non-peptide homing devices. Such RGD mimetics provide additional possibilities of introducing structural elements and are metabolically more stable than peptides.…”
Section: Resultsmentioning
confidence: 99%
“…The differences in integrin expression between these cells could play a role in the differences in binding, as integrins might have their unique optimal special presentation. 49 Additionally, phase-separated vesicles containing DSPE-RGD did not bind stronger than uniform DSPE-RGD vesicles in either cell type. FRET analysis to confirm lipid domains demonstrated that DSPE-RGD phase-separated vesicles did exhibit domain formation (Figure S5).…”
Section: Resultsmentioning
confidence: 91%
“…We created uniform and phase-separated vesicles with 10 mol% DOPE-RGD, confirmed phase separation using FRET (Supporting Figure S5), and tested binding to Jurkat and K562 cells, cell lines that both highly express the RGD-binding integrin α 5 β 1 . 49 In uniform vesicles, 10 mol% RGD vesicles exhibited minimal binding on both Jurkat and K562 cells compared to unfunctionalized control vesicles (Figure 4b-e). When RGD was concentrated into lipid domains, binding was greatly enhanced to Jurkats (~15 fold) and K562s (~5 fold) (Figure 4b-e).…”
Section: Phase Separation Can Enhance Binding Of Vesicles With a Ther...mentioning
confidence: 93%
See 1 more Smart Citation
“…Fibronectin concentration is vital to affect the migratory characteristics of the Jurkat cells. CD49e/CD29 (α5β1, VLA-5), which recognizes the RGD-containing fibronectin binding site, and CD49d/CD29 (α4β1, VLA-4), which binds the CS-1 region on fibronectin [ 23 ], control the cells’ attachment and migration movements according to the leukocyte activation status [ 24 , 25 , 26 ]. In this case, we applied a relatively high concentration of fibronectin coating in microchannels for 1 h, and repeated the flash every 10 min with fresh fibronectin solution to achieve the required surface coating density in the channels.…”
Section: Notesmentioning
confidence: 99%